The Application of Picture Media to the Beginning Reading Skills of SD 106 Pongsamelung Students, Luwu Regency - Yusni (Jurnal Multidisiplin Madani, 2022)
This study aims to describe the beginning reading skills of 106 Pongsamelung Elementary School students. The research method used is descriptive qualitative. The data of this study were students of Elementary School 106 Pongsamelung, using observation, interview and documentation data collection techniques. The data analysis technique uses the Milles and Huberman model with the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that early reading learning for grade I students is urgently needed to prepare for the advanced reading stage, because students will have difficulty following and understanding the subject matter if they cannot read, so beginning reading is a student's obligation. Beginning reading learning should be carried out with fun methods and media images for students, so that students do not feel burdened and pressured in learning to read